Individual Approach to the Treatment of Complicated Forms of Blepharitis: from Theory to Practice - E. A. Drozdova; E. V. Mikhailova (Oftalʹmologiâ, 2020)
High prevalence of blepharitis, multifactorial etiology and chronic course with the possibility of serious complications, including conjunctivitis, multiple chalazions, keratitis, dry eye syndrome — cause significant difficulties in the treatment of this disease. Prescribing treatment of the process only in case of exacerbation with the use of even modern antimicrobial and anti-inflammatory drugs gives only a short-term effect.The aim is to present the clinical features of the blepharitis of different localization and the choice of the optimal treatment algorithm on the example of specific clinical cases. The article presents current data on the classification, etiology and mechanism of blepharitis development. Based on a detailed description of two clinical cases of blepharitis, the features of the clinical course, the range of necessary examinations and consultations of specialists are presented. The first case describes blepharitis associated with the severe rosacea in a teenager with a typical complication in the form of rosacea — keratitis. The second case is devoted to the features of the posterior blepharitis clinical course with meibomian gland dysfunction, complicated by multiple chalazions. The article explains in detail the stages of prescribing various medications, including eyelid hygiene, antibacterial, anti-inflammatory therapy and artificial tears, discusses possible side effects of the therapy and ways to restore the eye surface.Conclusion. The basis of blepharitis treatment is regular three-component eyelid hygiene. In case of exacerbation it is advisable to prescribe antibacterial and anti-inflammatory drugs, taking into account the sensitivity and ability to destroy microbial biofilms. In order to increase patient adherence to treatment, the choice of hygiene products and moisturizing drops should take into account the tolerability of the drug and the convenience of its use.